The relationship between health literacy and quality of life in retirement of Rafsanjan University of Medical Sciences - Fatemeh Hosieni; Tybeh Mirzaei; Ali Ravari; Ali akbary (Mashhad University of Medical Sciences, 2016)
Background and objective: Health literacy of individuals have the capacity to obtain, process and understand basic information to decide an appropriate health service in this area is necessary. This study aimed to determine the association between health literacy and quality of life in retirement Rafsanjan University of Medical Sciences. Methods: This cross-sectional study on 137 retirees of the city of Rafsanjan University of Medical Sciences. The sampling method was census. The validity of the questionnaire Functional Health Literacy Adult TOFHLA, and the questionnaire was 36 SF. Information collected through SPSS18 software and using ANOVA statistical tests, and chi-square and Pearson correlation and regression analysis. Results: Total score quality of life and level of health literacy in retirement for the 58.9047 and 57.07± 60.45 respectively. Health literacy as a predictor of quality of life score ( p=0/001 and  r =0/64). One-way analysis of variance between health literacy and age, and chi-square test showed that the variables life style, education, efficient your knowledge, has a significant relationship with the disease. However, health literacy level variables marital status, sex, satisfaction with the economic situation, and the drug had no significant relationship. Conclusion: Retirement planning in order to increase the level of health literacy can enhance their quality of life Keywords: seniors, health literacy, and quality of life. Paper Type: Research Article.